2013
DOI: 10.1111/cjag.12024
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Labor Price Change on Agricultural Machinery Usage in Chinese Agriculture

Abstract: The substitution between rural labor and machinery has been a key determinant of farm production, structure, and efficiency in most developed countries and is expected to play a key role in shaping the future of Chinese agriculture. Using disaggregated farm-level data from Hebei and Shandong provinces of China, we calculated the Allen and Morishima elasticities of substitution between labor and machinery. These elasticities were based on seemingly unrelated regressions and three-stage least squares estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 54 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…Microeconomic production theory shows that demand for production factors is infl uenced by the price of factors themselves and the price of other factors. The degree of response of factor demand to its price change is the price elasticity of demand, which is the ratio between the percentage of change in factor demand and the percentage of change in factor price (McFadden, 1963;Liu et al, 2014): if the demanded quantity of a factor exhibits a large change in response to changes in its price, it is termed elastic, if the demanded quantity of a factor show a small change in response to changes in its price, it is termed inelastic. Given the output level, the degree of response of factor demand to price changes in other input factors is the elasticity of substitution, which is the ratio between the percentage of change in factor demand and the percentage of change in price of other factors (Binswanger, 1974;Clark et al, 2013): if the price of factor A declines and producers are encouraged to increase the input of factor B, then there is a complementary relationship between factors A and B; if the opposite is true, there is a substitution relationship between factors A and B.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Microeconomic production theory shows that demand for production factors is infl uenced by the price of factors themselves and the price of other factors. The degree of response of factor demand to its price change is the price elasticity of demand, which is the ratio between the percentage of change in factor demand and the percentage of change in factor price (McFadden, 1963;Liu et al, 2014): if the demanded quantity of a factor exhibits a large change in response to changes in its price, it is termed elastic, if the demanded quantity of a factor show a small change in response to changes in its price, it is termed inelastic. Given the output level, the degree of response of factor demand to price changes in other input factors is the elasticity of substitution, which is the ratio between the percentage of change in factor demand and the percentage of change in price of other factors (Binswanger, 1974;Clark et al, 2013): if the price of factor A declines and producers are encouraged to increase the input of factor B, then there is a complementary relationship between factors A and B; if the opposite is true, there is a substitution relationship between factors A and B.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…As an important factor in agricultural production, the demand for fertilizer is closely related to the price of fertilizer, labour and machinery faced by farmers in production decisions (Liu et al, 2014;Hu and Yang, 2015;Gao et al, 2018). Considering the following general representative household agricultural production decision-making model:…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It is generally suggested that there is a substitute relationship between labour and fertilisers. When labour is shortage, in order to maintain food production, farmers often tend to add more fertiliser per unit area of soil to make up for the lack of labour input (Liu et al, 2014;Wang et al, 2019), which further induces agricultural technology progress towards the fertiliser-using, aggravating agricultural non-point source pollution (Xiang et al, 2020). On the contrary, increasing the labour capital ratio will promote fertiliser-saving technological progress.…”
Section: Benchmark Regress Resultsmentioning
confidence: 99%
“…Particularly under China's current household registration system, rural labourers entering urban employment still maintain arable soil and work part-time in agricultural production activities, which makes it difficult to transfer and concentrate soil and limits the substitution of machinery for labour (Ito, 2010;Li et al, 2017). In order to maintain food production, farmers often tend to add more fertiliser per unit area of soil to make up for the lack of labour input (Liu et al, 2014;Wang et al, 2019), which further induces agricultural technology progress towards the fertiliser-using, aggravating agricultural non-point source pollution (Xiang et al, 2020). At the same time, however, scholars have found that there is a negative correlation between land and fertiliser, with a significant 0.5% reduction in fertiliser and pesticide use for every 1% expansion of land area (Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Economic mechanisms, preconditions, and methodological aspects of business development in the agricultural machinery market under modern economic conditions have been studied in multiple works, including (Bortolini, Cascini, Gamberi, Mora, & Regattieri, 2014a;Huang, Yun, You, & Wu, 2011;Liu Hu, Jetté-Nantel, & Tian, 2014;Staus & Becker, 2012;Yakymenko, 2013;Yu, Leng, & Zhang, 2012;Zhovnovach, 2014). In the agricultural machinery market, machinery and agricultural equipment is bought and sold (Muzlera, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%